Sosialisasi dan Penyuluhan Gerakan Menabung Sejak Dini di Panti Asuhan Al Hayyat, Magetan - Dwi Nila Andriani; Ramadhan Prasetya Wibawa; Meilani Alda Saputri; Yahya Sarul (Universitas Kristen Indonesia Toraja, 2024)
Socialization is a means of the learning and teaching process. The purpose of socialization and counselling is to provide individuals and community groups with an understanding of something. Saving is essential in terms of financial management. Saving is setting aside money for a certain period that can be used. Knowledge about finances is not only intended for adults or parents, but young children need to be given understanding and good habits that can be useful in later life. The targets for this activity are the children of the Al Hayat Orphanage in the Milangasri District, Panekan District. Magetan. The number of participants was 28 people, consisting grade elementary school to high school. This activity benefits children at the Al-Hayat Magetan Orphanage to be more creative in processing used goods into valuable products even though they are not of high value. Apart from that, this activity is hoped to inspire others to see creative potential in things that are usually considered waste or rubbish.